Respect and Retribution: Legal Punishment in The Metaphysics of Morals - Mañalich, Juan Pablo (Revista de Ciencia Política, 2018)
The paper offers a reading of the section of the The Metaphysics of Morals in which Kant advances a secular conception of the legitimation of legal punishment, based upon the postulation of a (meta-)principle of respect as normative premise. On this basis, the precise meaning of the characterization of penal law as a “categorical imperative” is addressed, as well as the status of the “right of retribution” as standard for the commensuration of punishment. In this way, the paper seeks to undermine the linkage of Kant’s conception with the leitmotiv of a metaphysical realization of justice, as well as its interpretation as a version of a mixed theory, which would allegedly combine a deterrence goal with a mere side-constraint of desert-based proportionality.